`Embracing turbulent waters`: Enhancing athlete self-regulation using the `PoST` framework for performance preparation at the 2020 Tokyo Olympic Games - Morris, C. E.; Otte, F. W.; Rothwell, M.; Davids, K. (Asian Journal of Sport and Exercise Psychology, 2022)
Sport science has increasingly witnessed use of contemporary ecological approaches to athlete development, preparation, and skill acquisition, providing alternatives to traditional pedagogical approaches. Here we examine an ecological perspective on transferring theory into coaching practice for athlete self-regulation and performance preparation, by presenting the case example of one lead coach and three athletes representing Team GB in the sport of Canoe Slalom at the 2020 Olympics in Tokyo. The aims of this case exemplar are: (1) to offer insights into how an ecological dynamics rationale supported integration of nonlinear pedagogy and (skill) training periodisation, underpinning athlete preparation for world class Canoe Slalom competition; and (2), to provide a first-hand perspective on transfer of theory to support self-regulation, skill learning, and performance preparation in high-performance sport. In the case example, the `Periodisation of Skill Training` framework (i.e., termed `PoST` framework) for venue specific preparation at the Tokyo Olympics was applied and adapted. Principles of co-design, the Constraints-Led Approach, perception-action coupling and representative learning design were embedded within collaborative application of the framework across a support team including athlete, coach and psychologist. To conclude, facilitating athlete self-regulation is highlighted in practical exemplars to support paddlers to cope with the dynamic environments in canoe slalom.